Development of Magnetite Nano–composite Membrane for Membrane Defouling - Azmi, N. A.; Ng, Q. H.; Ahmad, A. L.; Low, S. C. (Journal of Applied Membrane Science & Technology, 2017)
This research proposes to untangle the membrane fouling by introducing nanostructured magnetite (Fe3O4) colloids into the polymeric membrane. In present study, nanostructure magnetite nanoparticles (MNPs) were synthesized via co–precipitation method with ammonium hydroxide and sodium hydroxide as the precipitation agents at different pH condition. The synthesized MNPs were functionalized with poly(diallyldimethylammonium chloride) (PDDA) and then spin coated on the surface of the ultrafiltration cellulose acetate (CA) membrane. Intrinsic properties for this nano–composite membrane, in regards to the physical structures, surface negative charge density and the membrane filtration performance, on surface fouling by humic acid solutions were investigated. Experimental results demonstrated that, the nano–composite membrane has significantly reduced the humic acid fouling on the membrane surface. This could be explained by the electrostatic interactions between negatively charged humic acid molecules and the nano–composite membrane. Throughout the study, the results provide some fundamental insights into the physical interactions that governing the membrane fouling during filtration.